ASSESSING THE KNOWLEDGE OF SMALLPOX AND MONKEYPOX VIRUS AMONG THE UNIVERSITY OF TLEMCEN MEMBERS IN THE WAKE OF COVID-19: A 2023 CROSS-SECTIONAL STUDY.: a Cross-sectional Study - ZATLA, Ilyes; ABID, Wafa; BOUBLENZA, Lamia (African Journal of Infectious Diseases (AJID), 2023)
Background: A recently-surfaced virus called Monkeypox virus (MPXV) has gained widespread attention as it dominates the news, creating a sense of panic among people due to the potential threat it poses to their health. Materials and Methods: To evaluate knowledge about this virus and its disease, and to raise consciousness among the members of the Faculty of Natural and Life Sciences and Earth and Universe Sciences at the University of Tlemcen, we launched an online web-based survey for a twenty days’ period that contained sociodemographic and perceptiveness questions about the emergent virus, its disease, and vaccination. Results: Our findings showed that the majority of the respondents of our study have a satisfactory level of knowledge about this emerging virus and its disease. Moreover, most participants showed a positive attitude towards the vaccine, considering it the best preventive means to fight against Monkeypox disease. Conclusion: Although the MPXV may not become a pandemic, but knowing the various ways that contribute to its spread is essential to avoid any possibility of a new one, especially in Algeria.